A supervised internship that articulates teaching-learning and research: Senses, relationships, and meanings mobilized by a physics student in Brazil - Karsten, Karine (2023)
In order to defend the importance of teacher training from critical and transformative perspectives, we report in this article a research that aimed to understand the instruments that enhance such training. With a qualitative approach and a case study methodology, we analyzed how and which senses were constructed by a Physics undergraduate student during his teaching internship. We identified the instruments that influenced the student in the attribution of senses that brought him closer to being a transforming intellectual. The research was carried out at a public university in the city of Curitiba, Brazil, in the years 2019 and 2020. The empirical procedures used were: participant observations, researchers’ notes, analysis of documents produced by the student during his internship, questionnaires, and semi-structured interviews. By analyzing the mobilized senses, we observed the importance of the following instruments: different ways of systematizing the intern’s experiences; carrying out a collective, dialogic and autonomous teaching practice; articulation between teaching and research in teaching practices; and valuing the supervising teacher in the internship guidance process. We concluded that teaching linked to research, with strong care for the relationships between subjects in the internship, intensifies knowledge about the teaching and learning process. With these instruments highlighted, it becomes possible to rethink the organization of internship activities, seeking to develop actions that are intentionally consistent with the teacher training proposal with potentially critical and transforming senses.